Relationship between Housewife Behavior in Using Clean Water and Diarrhea in Toddlers (0-59 Months) at Sukamulya Public Health Center, Singkup District, Ketapang Regency - subardi; khayan; Paulina (Jurnal teknologi Kesehatan Borneo, 2021)
Diarrhea is one of the leading causes of morbidity and mortality, especially in children under five. Some of the causes of disease are clean water and disposal of feces, both of which are influenced by human behavior. This research is research using the observational method with a case-control study design. The samples taken in this study were toddlers (0-59 months) who suffered from diarrhea and the houses around the patients who did not have diarrhea. The data used in this study is secondary data from related agencies and primary data obtained from interviews and observations. From the survey results, 31.1% suffer from diarrhea, and 68.9% are not sick. Then from the bivariate results with X2 5% analysis received four variables that are not related to diarrheal disease in toddlers, namely the variable of using clean water sources (0.297), behavior variable choosing clean water (0.227), behavior variable transporting clean water (1,000), behavioral variable using clean water (0.073) and one related variable, namely the variable protecting clean water (0.021).